Mesocolic Lymph Node Number, Size, and Density. Issue 8 (August 2015) - Ahmadi, Omid; McCall, John L.; Stringer, Mark D.
<x xml:space="preserve">Abstract</x> BACKGROUND: Lymph nodes play a critical role in the staging, treatment, and prognosis of colon cancer. However, the normal number and morphology of lymph nodes in the normal mesocolon is unknown. OBJECTIVE: This study aimed to investigate the number and size of lymph nodes in the ascending and sigmoid mesocolons. DESIGN: This is a descriptive anatomical cadaver study of 10 sigmoid mesocolons and 5 ascending mesocolons, resected in a standardized manner and examined systematically after serial histological sectioning. The number, maximum length, and appearance of lymph nodes were analyzed, and the 2 mesocolons were compared by using the Mann-Whitney U test, the Wilcoxon signed rank test, and the χ2 test. PATIENTS: Ten cadavers (mean age, 82.9 years; 5 male) with no evidence of colorectal disease were examined. MAIN OUTCOME MEASURE: The number, maximum length, and appearance of lymph nodes and fat-associated lymphoid clusters were the primary outcomes measured. RESULTS: The median number of lymph nodes in the sigmoid and ascending mesocolons was 71 (range, 24–116) and 61 (range, 33–71). More than 90% of lymph nodes were less than 5 mm in maximum length. Sigmoid mesocolic nodes were significantly smaller than ascending mesocolic nodes (median maximum lymph nodes length, 1.6 mm vs 2.1 mm; p < 0.001), but there was no statistically significant difference in the density of lymph nodes between the sigmoid and ascending mesocolon. Fatty replacement was seen in almost 30% of lymph nodes. A few fat-associated lymphoid clusters were observed in both mesocolons. LIMITATIONS: Only 15 mesocolic specimens could be examined because of the detailed labor-intensive methodology, and younger cadavers were not available for analysis. CONCLUSIONS: In this descriptive anatomical study, the median number of lymph nodes in the sigmoid and ascending mesocolon was 71 and 61. Ascending mesocolic nodes were significantly larger than sigmoid mesocolic nodes. These anatomical findings are relevant to the interpretation of lymph node yields after the surgical resection of colon cancer.